Meeting Gorbachev [videorecording (DVD)] - Herzog, Werner, 1942-; Herzog, Werner, 1942-; Gorbachev, Mikhail Sergeevich, 1931-; Reagan, Ronald; Thatcher, Margaret; Wałęsa, Lech, 1943- (Passion River, 2019)
Werner Herzog and Andre Singer's riveting documentary, filled with unforgettable archive materials and based on three never before seen interviews, provides incredible access to, arguably, the world's greatest living politician. Now 88 and battling illness, the visionary Gorbachev, the former General Secretary of the U.S.S.R, is still gently but resolutely pushing towards his goals.